Matrona taoi spec. nov., a new damselfly species from northern Vietnam (Odonata: Calopterygidae) - Phan, Quoc Toan; Hämäläinen, Matti (Zootaxa, 2011)
Matrona taoi Phan & Hämäläinen, spec. nov. (holotype ♂ , from Vietnam, Phu Tho province, Xuan Son National Park, Xom Coi, alt. 442 m, 15 xi 2010, deposited in Vietnam National Museum of Nature, Hanoi) is described from both sexes, illustrated and compared with other species in the genus.